Specialized Therapeutic Assessment-Based Recovery-Focused Treatment for Young People With Self-Harm: Pilot Study - English, Oliver; Wellings, Christy; Banerjea, Partha; Ougrin, Dennis (Frontiers in Psychiatry, 2019)
Background: Suicide is the second leading cause of death in young people worldwide. Self-harm is the strongest predictor of death by suicide. There is increasing evidence that psychological therapies are efficacious in treating self-harm in adolescents. However, studies so far have predominantly focused on highly selective groups of adolescents and have investigated interventions that require considerable training and expense. Methods: We conducted a pilot study of a novel psychological therapy package, START that consists of Therapeutic Assessment (TA) followed by treatment in one of three modules, depending on adolescents’ needs and preferences: Solution Focused Brief Therapy (SFBT), Cognitive Behaviour Therapy (CBT) or Mentalization Based Treatment (MBT). Adolescents (12-17) with at least one self-harm episode in the previous six months referred for community treatment, who had no intellectual disability, psychosis or autism were eligible for START. The primary outcome measure was the number of self-harm episodes 6 months before and 6 months after commencing START. Secondary outcomes included measures of psychopathology, functional impairment and family satisfaction. Results: 21 consecutively referred adolescents were recruited, 18 were thought to require a community intervention and 15 received START: 3 received SFBT, 9 CBT and 3 MBT. There was a statistically significant reduction in the number of self-harm episodes from a mean of 7.93 (SD=12.26) to 1.00 (SD=1.47), p<0.02 following START. There was also a significant reduction in self-harm episodes, Revised Children’s Anxiety and Depression Scale (RCADS) scores and a statistically significant improvement in Children Global Assessment Scale (CGAS) scores for the CBT group alone. There were no significant differences in any other outcomes. Most families were somewhat or very much satisfied with the intervention. Conclusion: The results show that START could be successfully used in a community mental health setting. START was associated with a meaningful reduction in self-harm and depression and anxiety symptoms but no improvements in other outcomes. These findings indicate that START should be rigorously studied in a randomized control trial (RCT). CBT was the most frequently used module within the START package and could be the most promising treatment for adolescents with self-harm referred to community mental health services.